Analysis of Supply Chain Management Performance using SCOR and AHP Methods In Green Avenue Apartments of East Bekasi - Anjas Handayani; Christianto Yuppie Setyatama (Journal of Applied Science, Engineering, Technology, and Education, 2019)
This study analyzes the performance of a company's supply chain as measured by an approach using the SCOR method or the Supply Chain Operations Reference. SCOR is divided into 5 basic supply chain management processes, namely plan, source, make, deliver and return. Due to schedule delays of 3%, it is affected by the late delivery of raw materials ordered from suppliers and the quality of raw materials is below standard. Performing a performance measurement approach is also supported by the Analytical Hierarchy Process (AHP) method to determine the weight of each performance indicator and is calculated using the Expert Choice v11 program in this study. The purpose of this study was to determine how much value the PT Adhi Commuter Properti supply chain performance and what performance indicators should be improved. The results of the study resulted in a 75.444 overall supply chain performance achievement score of the GOOD category in achieving total company performance appraisal and priority improvement recommendations of 4 performance indicators that are expected to help improve the company's supply chain performance, namely the fulfillment of raw materials, structures, defective products and demand that the company can fulfill.